Enabling a stable room-temperature sodium-sulfur battery cathode by building heterostructures in multichannel carbon fibers - Ye, Xin (2022)
Room-temperature sodium-sulfur (RT Na-S) batteries are widely considered as one of the alternative energy-storage systems with low cost and high energy density. However, the both poor cycle stability and capacity are two critical issues arising from low conversion kinetics and sodium polysulfides (NaPSs) dissolution for sulfur cathodes during the charge/discharge process. Herein, we report a highly stable RT Na-S battery cathode via building heterostructures in multichannel carbon fibers. The TiN-TiO2@MCCFs, fabricated by electrospinning and nitriding techniques, are loaded with the active material S, forming S/TiN-TiO2@MCCFs as the cathode in a RT Na-S battery. At 0.1 A g-1, the cathode produces the capacity of more than 640 mAh g-1 within 100 cycles with a high Coulombic efficiency of nearly 100%. Even at 5 A g-1, the battery still exhibites a capacity of 257.1 mAh g-1 after 1000 cycles. Combining structural and electrochemical analyses with the first-principles calculations reveals that the incorporation of the highly electrocatalytic activity of TiN with the powerful chemisorption of TiO2 well stabilizes S and also alleviates the shuttle effects of polysulfides. This work with simple processes and low cost is expected to promote the further development and application of metal-S batteries.